Wind farm noise prediction and auralization - Bresciani Andrea P. C.; Maillard Julien; Finez Arthur (Acta Acustica, 2024)
This work presents the application and validation of a novel auralization approach for the evaluation of wind turbine noise annoyance under diverse conditions. The approach is based on the decomposition of each turbine blade into elementary short-segment sources, whose acoustic radiation in the far field is obtained by coupling Amiet’s emission model with the Harmonoise engineering model for outdoor sound propagation. The transfer functions between the elementary source positions and receivers are obtained. Then, the average and instantaneous sound pressure levels are calculated over one blade rotation. The realism of the audio signals is evaluated through listening tests with audio signals of the real and simulated environments. The predicted noise spectra from five wind turbines capture well the measured trends and the absolute levels. Finally, we present a study of the weather effects on noise emissions and propagation by using the numerical model developed.